Investigation of Gait Characteristics and Kinematic Deviations in Rare Genetic Disorders with Instrumented Gait Analysis. - Kınacı‐Biber, Esra; Gys, Lis; Jansen, Anna C.; Schoonjans, An‐Sofie; Van Dijck, Anke; Kooy, R. Frank; Van de Walle, Patricia; Hallemans, Ann (Journal of Intellectual Disability Research, 2025)
Background: Dravet Syndrome (DS), Helsmoortel‐Van Der Aa Syndrome (HVDAS) and Tuberous Sclerosis Complex (TSC) are rare genetic syndromes, sharing intellectual disability (ID) and motor delay. In DS, two distinct gait patterns, crouch and non‐crouch, have been described using instrumented 3D gait analysis (i3DGA). This cross‐sectional study measures gait in participants with TSC and HVDAS. The findings are compared to the known crouch and non‐crouch gait patterns observed in DS and to typical gait. Methods: Participants (6–22 years) with DS (n = 37; 19 crouch and 18 non‐crouch), HVDAS (n = 12) or TSC (n = 8) were compared with typically developing (TD) peers (n = 33). All participants underwent i3DGA (Plugin Gait model processed with Vicon Nexus and MATLAB®) to investigate spatiotemporal and lower‐limb kinematics. Results: All three genetic syndromes showed increased step width. Participants with HVDAS and DS, but not participants with TSC walked with decreased step length and velocity compared to TD. HVDAS demonstrated increased knee flexion during the stance phase, lack of hip extension during pre‐swing, and increased ankle dorsiflexion during some phases of the gait cycle (p < 0.001). Additionally, HVDAS showed similar kinematic deviations to DS‐NonCrouch. No significant differences were found in terms of kinematics between TSC and TD peers (p > 0.05). Conclusion: The current study reveals differences in gait characteristics from typical functional gait in rare genetic disorders. DS‐Crouch, DS‐NonCrouch and HVDAS display a more impaired gait from a biomechanical perspective than TSC. The variability of clinical and genetic features might explain heterogeneity in gait deviations and should be further explored.